Composition and Zonation of Mangrove Vegetation in Ujung Pangkah, Gresik, Indonesia - Mabruroh, Arofatul Syabina; Firdhausi, Nirmala Fitria; Bahri, Saiful; Rachmawati, Yuanita; Munir, Misbakhul (Universitas Muhammadiyah Surakarta, 2024)
Ujung Pangkah Gresik is a significant mangrove area with both ecological and economic functions. Ecologically, it prevents seawater intrusion and abrasion, while economically, it supports sectors like tourism, forestry, fisheries, and ecotourism. This research aims to identify mangrove species diversity and zoning patterns in Ujung Pangkah using survey methods to assess diversity, density, dominance, importance value, and zoning. Four species were found (Avicennia marina, Avicennia officinalis, Rhizophora stylosa, Ceriops tagal) with 454 individuals. The diversity value is moderate at 1.86. The highest and lowest densities were 0.52 and 0.01, respectively. Avicennia marina is the dominant species with an importance index of 273.69. The area has a mixed zoning pattern.